Diesel engine and fuel system repair - Dagel, John F (Regents/Prentice Hall, 1994)
This cutting-edge manual incorporates the latest in diesel engine technology, giving readers a solid introduction to the technology, operation, and overhaul of heavy duty diesel engines and their respective fuel and electronics systems.